2019
DOI: 10.1371/journal.pone.0213006
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of vitamin D supplementation in gestational diabetes mellitus: Systematic review and meta-analysis of randomized trials

Abstract: BackgroundTrials have examined on the benefits of vitamin D supplementation in pregnant women.ObjectiveThis review aimed to evaluate whether oral vitamin D supplements, when given to pregnant women with gestational diabetes mellitus (GDM), would improve maternal and neonatal outcomes, compared with no treatment or placebo.MethodWe performed a systematic review following Cochrane methodology, and randomized trials were included where pregnant women with GDM received vitamin D supplementation versus placebo/no t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 31 publications
0
20
0
2
Order By: Relevance
“…They suggested that vitamin D supplementation may reduce gestational diabetes, low birthweight, and preeclampsia, but a higher than currently recommended dose appeared to have no additional benefit except for possible further reduction of gestational diabetes [74,75]. However, several studies in recent years have highlighted that women are at high risk for vitamin D deficiency, and this is associated with adverse pregnancy outcomes, including preeclampsia and gestational diabetes [76][77][78][79][80]. It has been demonstrated that vitamin D supplementation is able to reduce adverse pregnancy outcomes when a higher level is achieved, with an increasing efficacy when the target level is raised from 20 to 40 ng/mL or 50 ng/mL.…”
Section: Pregnancymentioning
confidence: 99%
“…They suggested that vitamin D supplementation may reduce gestational diabetes, low birthweight, and preeclampsia, but a higher than currently recommended dose appeared to have no additional benefit except for possible further reduction of gestational diabetes [74,75]. However, several studies in recent years have highlighted that women are at high risk for vitamin D deficiency, and this is associated with adverse pregnancy outcomes, including preeclampsia and gestational diabetes [76][77][78][79][80]. It has been demonstrated that vitamin D supplementation is able to reduce adverse pregnancy outcomes when a higher level is achieved, with an increasing efficacy when the target level is raised from 20 to 40 ng/mL or 50 ng/mL.…”
Section: Pregnancymentioning
confidence: 99%
“…It is hypothesized that the role vitamin D plays in modulating immune function and preventing inflammation is the likely mechanism for which vitamin D supplementation in protecting maternal and fetal health [15]. Wagner et al have demonstrated that an intake of 4000 IU/d during pregnancy, to achieve a serum 25(OH)D above 40 ng/mL (100 nmol/L), can reduce the incidence of preterm by more than half [16] and may reduce other complications of pregnancy including preeclampsia, gestational diabetes and possibly post-partum hemorrhage [17][18][19]. Their findings have resulted in a vitamin D supplementation program (in place since 2017), wherein 5000 IU/d of vitamin D is provided to all pregnant women, implemented at five hospitals within the Medical University of South Carolina [20].…”
Section: Vitamin D and Pregnancymentioning
confidence: 99%
“…Varying blood collection periods and characteristics of the participants (the latter excluding preterm SGA infants) might have contributed to the differences in the study results. [17]. Moreover, a cohort study based on a prospective community research did not find any evidence showing that vitamin D status during early pregnancy was associated with pregnancy-related hypertension in women who did not have children [18].…”
Section: Discussionmentioning
confidence: 94%